Simulation and energy optimization in a pulp and paper mill : Evaporation plant and digester - Ji, Xiaoyan; Lundgren, Joakim; Wang, Chuan; Dahl, Jan; Grip, Carl-Erik (Luleå tekniska universitet, Energivetenskap, 2011)
A mathematical process integration model of a pulp and paper mill in the Northern Sweden has been developed. The main modelling focus has been put on the two main steam consumers (the evaporation plant and the digester), for which detailed material and energy balances have been established. Operational data have been used to validate the simulation results. By implementing these submodels into the complete plant model, the influence of different operation parameters on the overall plant performance has been investigated. Furthermore, introductory studies with the main objective to minimize the plant energy cost have been carried out. The correlation and differences between economic and energy have been discussed Godkänd; 2011; 20120131 (xiajix)